2017
DOI: 10.1128/jcm.00579-17
|View full text |Cite
|
Sign up to set email alerts
|

French Prospective Clinical Evaluation of the Aptima Mycoplasma genitalium CE-IVD Assay and Macrolide Resistance Detection Using Three Distinct Assays

Abstract: The aim of this study was to evaluate the clinical performance of the Aptima Mycoplasma genitalium transcription-mediated amplification (MG-TMA) CE-marked for in vitro diagnosis (CE-IVD) assay for the detection of Mycoplasma genitalium in male and female clinical samples in comparison with the in-house real-time PCR (in-house PCR) assay routinely used in our laboratory. A total of 1,431 clinical specimens obtained from 1,235 patients were prospectively collected at the Bacteriology Department of Bordeaux Unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“…Overall, the results reported in this evaluation were in agreement with previously reported sensitivity and specificity rates for this assay10; however, we found the assay to be more sensitive for macrolide-genotype detection than Le Roy et al (2017) 11…”
Section: Discussionsupporting
confidence: 92%
“…Overall, the results reported in this evaluation were in agreement with previously reported sensitivity and specificity rates for this assay10; however, we found the assay to be more sensitive for macrolide-genotype detection than Le Roy et al (2017) 11…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we validated the performance characteristics of four TMA NAAT assays for the detection of ribosomal RNAs from M. genitalium. We found that these assays are sensitive and specific for the detection of multiple stains of M. genitalium and have Similarly to NAATs designed to detect other sexually transmitted infections such as Chlamydia trachomatis, Neisseria gonorrhoeae, and Trichomonas vaginalis, the detection of rRNA of M. genitalium affords a particularly sensitive method for detecting the organism in vivo, leading to improved clinical diagnosis of M. genitalium infection compared to that with NAATs that target genomic DNA of the organism (20)(21)(22). This difference in relative test clinical sensitivity may be due to the disparity between genomic DNA and rRNA content in the cell (i.e., a single DNA genome versus an estimated hundreds to thousands of rRNA copies per cell) (29), enabling the detection of low titers of M. genitalium in patient specimens (30,31).…”
Section: Discussionmentioning
confidence: 97%
“…This is the first study to use only rRNA-specific NAATs for the components of a composite comparator reference standard for the evaluation of an rRNA-based molecular test for M. genitalium detection. Previous studies investigating the clinical perfor- mance of rRNA-based NAAT assays for M. genitalium used a reference standard consisting of a combination of tests that detected rRNA and genomic DNA of M. genitalium (20,21). This mixed reference standard approach has the potential to introduce bias into the analyses, since the lower sensitivity of DNA-based tests can decrease the rate of DNA-positive/RNA-positive consensus results obtained in the analysis, potentially resulting in artificially lowered specificity estimates for the RNA-based diagnostic test under evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations